Analisis Kebutuhan Ruang Terbuka Hijau Berdasarkan Emisi CO2 dari Konsumsi Energi Kegiatan Permukiman di Kecamatan Pamulang Kota Tangerang Selatan - Salsabila Ranupuspa; Irland Fardani (UNISBA Press, 2023)
Abstract. Pamulang District as the area with the highest number and population density in South Tangerang City encourages high interaction, mobilization and use of energy, especiallu energy from urban activities which has an impact on air pollution and contributes to the formation of the condition of South Tangerang City as a city with the worst air quality in Indonesia based on IQ Air Survey on 2019. This analysis uses the IPCC Guidelines 2006 method to determined the amount of CO2 emissions released from energy consumption of urban activities in Pamulang District. Based on the results of the analysis, it is known that the total of CO2 emissions from the residential activities in Pamulang District reach 1076402 ton.CO2/year. Existing green open space in Pamulang District which function as CO2 emission reduction are only able to absorb 22.094 ton.CO2/year, so it is necessary to develop green open space to be able to optimally reduce CO2 emissions from residential activities, namely by intensifying green open space which is focused on green open space along the Siliwangi Road corridor, open green space along rivers in Situ Pamulang and Angke River, and green open space around the monument and Alun-Alun Pamulang; as well as extending green open space in the form of an additional 151 Ha which can be optimized by developing vertical and roof garden. Abstrak. Kecamatan Pamulang sebagai wilayah dengan jumlah dan kepadatan penduduk tertinggi di Kota Tangerang Selatan mendorong tingginya interaksi, mobilisasi dan penggunaan energi khususnya energi dari kegiatan permukiman yang berdampak pada pencemaran udara serta memberi kontribusi terhadap terbentuknya kondisi Kota Tangerang Selatan sebagai kota dengan kualitas udara terburuk di Indonesia berdasarkan survey IQ Air 2019. Analisis ini menggunakan metode IPCC Guidelines 2006 dan Metode Box Model untuk mengetahui besaran emisi CO2 yang dikeluarkan dari konsumsi energi kegiatan permukiman di Kecamatan Pamulang. Berdasarkan hasil analisis, diketahui bahwa total emisi CO2 dari kegiatan permukiman di Kecamatan Pamulang mencapai 236.329 ton.CO2/tahun. Ruang terbuka hijau eksisting di Kecamatan Pamulang yang berfungsi sebagai pereduksi emisi CO2 hanya mampu menyerap 215.825 ton.CO2/tahun, sehingga dibutuhkan pengembangan ruang terbuka hijau agar mampu mereduksi gas emisi CO2 dari kegiatan permukiman secara optimal yaitu dengan intensifikasi RTH yang difokuskan pada RTH di sepanjang koridor Jalan Siliwangi, RTH sempadan sungai di Situ Pamulang dan Sungai Angke, serta RTH pada sekitar Tugu dan Alun-Alun Pamulang; serta dengan ekstensifikasi RTH berupa penambahan seluas 151 Ha yang dapat dioptimalkan dengan mekanisme taman vertikal dan taman atap.